A leitura da literatura negro-brasileira na escola : um universo de representatividade a ser explorado - Cardoso, Janaína Sabina (2024)
This Professional Master's Dissertation in Letters, entitled: Reading Afro-Brazilian Literature in Schools: A Universe of Representativity to Be Explored, presents a proposal for working with the book The Danger of a Single Story by Chimamanda Ngozi Adichie (2009) and the text Pixaim by Cristiane Sobral, in addition to the cinematic works Narradores de Javé and AmarElo: It’s All For Yesterday. The aim is to discuss reading practices capable of forming competent readers regarding themes related to antiracism and the appreciation of ethnic-racial diversity as tools for the construction of individual identities. This work is divided into two parts. The first chapter addresses the concept of reading and how to engage with Afro-Brazilian literature to strengthen the recognition and resistance of Black communities. The theoretical framework is developed based on the works of Solé (1998), Cosson (2014), Colomer (2007), and Rouxel (2012, 2019), along with Duarte (2022), Cuti (2010), and a brief analysis of Law 10.639/03 to contextualize Afro-Brazilian literature. The second part consists of a pedagogical workbook proposal with reading and writing activities designed for final-year students of basic education. The activities were implemented with a ninth-grade class from São Cristóvão Municipal School, located in the São Pedro community, a rural area of Monte Santo, Bahia. Finally, the dissertation includes a methodological analysis of the application of the pedagogical workbook and a synthesis of the experiences with Afro-Brazilian literature.